2023
DOI: 10.1371/journal.pmed.1004088
|View full text |Cite
|
Sign up to set email alerts
|

High PrEP uptake and objective longitudinal adherence among HIV-exposed women with personal or partner plans for pregnancy in rural Uganda: A cohort study

Abstract: Background In Uganda, fertility rates and adult HIV prevalence are high, and many women conceive with partners living with HIV. Pre-exposure prophylaxis (PrEP) reduces HIV acquisition for women and, therefore, infants. We developed the Healthy Families-PrEP intervention to support PrEP use as part of HIV prevention during periconception and pregnancy periods. We conducted a longitudinal cohort study to evaluate oral PrEP use among women participating in the intervention. Methods and findings We enrolled HIV–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…This may have been due to the HIV prevention and sexual health counseling that all women received as part of the parent study. Similarly, in a study conducted in Uganda that enrolled HIV-exposed women planning pregnancy and used a similar HIV risk perception scale, perceived HIV risk scores using a 6-item scale were high 33 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may have been due to the HIV prevention and sexual health counseling that all women received as part of the parent study. Similarly, in a study conducted in Uganda that enrolled HIV-exposed women planning pregnancy and used a similar HIV risk perception scale, perceived HIV risk scores using a 6-item scale were high 33 …”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in a study conducted in Uganda that enrolled HIV-exposed women planning pregnancy and used a similar HIV risk perception scale, perceived HIV risk scores using a 6-item scale were high. 33…”
Section: Discussionmentioning
confidence: 99%
“…Women may be motivated to use oral F/TDF for reasons that relate directly to the timing of HIV risk or to perceived benefit. For example, high uptake of F/TDF use was recently reported among HIV-exposed women with plans for pregnancy in rural Uganda . Sexual behaviors that expose women to HIV acquisition also change over time, as demonstrated in the HPTN 064 study, in which social factors were found to influence sustained high-risk behavior, and should be integrated into decisions about approach to PrEP use .…”
Section: Discussionmentioning
confidence: 99%
“…For the 46 participants who had tenofovir plasma data that were used in the group-based trajectory modeling (ie, not including those with concurrent tenofovir diphosphate measurements in DBS), participants with plasma concentrations greater than or equal to 40 ng/mL were assigned to the high adherence group. This threshold was selected based on prior studies suggesting that 40 ng/mL reflects recent adherence and that participants with pill coverage of at least 80% had plasma tenofovir concentration greater than 40 ng/mL . Participants with concentrations less than 40 ng/mL were included in the low adherence group.…”
Section: Methodsmentioning
confidence: 99%
“…A study in South Africa observed substantially higher uptake of PrEP at 84% within a trial setting with additional staff; however, it was not possible to assess pre-trial enrollment attrition to determine whether the trial enrolled a population of women more likely to accept PrEP ( 32 ). A Ugandan cohort assessing pre-conception PrEP use among predominantly sero-different couples with fertility intention observed high PrEP uptake at 90%, but did not assess uptake during pregnancy ( 33 ). Future studies should consider how staffing ratios impact not only PrEP uptake, but also upstream steps of PrEP screening, counseling, and offer within busy MCH/FP clinics and test strategies to improve service provision reach broadly without adding new HCW.…”
Section: Discussionmentioning
confidence: 99%